A critical view on the soil fertility status of minimum-till kikuyu-ryegrass pastures in South Africa - Swanepoel, Pieter A; du Preez, Chris C; Botha, Philip R; Snyman, Hennie A (African journal of range & forage science, 2015)
Cultivated pastures provide increased productivity and contribute inter alia to food security. Rangelands in the southern Cape region of South Africa have had a low animal production potential and were therefore improved through time as cultivated pastures. Initially, annual pastures were established by conventional tillage methods, but from the 1990s permanent pastures were established on a minimum-tillage regime. Lime and fertiliser guidelines, which were developed for annual pastures established by conventional tillage methods, were followed on minimumtillage systems, despite changes in the soil physical properties and stratification of biological parameters. The study aim was to survey the soil fertility of irrigated minimum-till kikuyu-ryegrass pastures in the southern Cape region. This study highlights changes in soil fertility and identified potential detrimental effects of elevated levels of extractable phosphorus and zinc, which were drastically increased in the topsoil layer. The necessity for remedial and preventative strategies to mitigate nutrient loading in cultivated pasture soil are stressed. Fertiliser guidelines should be applied strictly and should fit the farming system. In doing so, the dual goals of economic and ecological sustainability should be achieved.